Finding the Relationship Between News and Social Media Users’ Emotions in the COVID-19 Process - Müngen, Ahmet Anıl; Aygün, İrfan; Kaya, Mehmet (My University, 2020)
Nowadays, social media and online sharing sites are frequently used to share thoughts about daily events. Thanksto the posts made by internet users on these platforms, first, quite big data is generated to interpret the agenda.More than 10,000 comments of more than 5000 users made about COVID-19 from online websites between 15March and 15 May were collected in this study. Then, emotional analysis on these comments was carried out withBERT, GRU, LSTM and TF-IDF methods. The changes in the amount of user comments and the emotionsreflected by the comments have been associated with the actual events of these dates. It has been determined whichtypes of events affect users more. In addition, the emotional response changes of the users to the official COVID19 statistics were measured and the peak points of the emotional changes were determined. Finally, the emotionclassification methods applied were evaluated by user questionnaires and their successes were determinedaccording to F-Measure.
Keywords: İletişim; Bilgisayar Bilimleri; Yazılım Mühendisliği